The Effect Of Ethanol Extract From Lingzhi Fungi (Ganoderma Lucidum) Cianjur Isolate On Syndecan-1 Expressions In Kb CCL17 Oral Cancer Cell: Efek Ekstrak Ethanol Dari Jamur Lingzhi (Ganoderma Lucidum) Isolat Cianjur Terhadap Ekspresi Syndecan-1 Pada Sel Kanker Rongga Mulut Kb Ccl-17 - Ashar, Fadli; Widodo, Haris Budi; Wahyono, Daniel Joko; Ratnaningtyas, Nuniek Ina; Nawangtantrini, Gita; Novrial, Dody; Dwiandhono, Irfan (TALENTA, 2021)
Intercellular adhesion plays a role in cancer formation and protein has a key potential in maintaining cell adhesion, including syndecan-1. Meanwhile, oral cancer originates from the oral epithelium, which has an invasive and metastatic level. Its treatments involving chemotherapy and radiotherapy commonly leave unfavorable side effects, hence, suitable alternatives are needed. Natural ingredients are widely used as an alternative treatment for cancer, for example, Ganoderma lucidum (G. lucidum) which has anti-cancer and anti-angiogenic properties, induces apoptosis, stimulates an immune response, inhibits the degradation of Extracellular matrix (ECM), reduces inflammation, affects cell cycles, cytotoxic, and acts as an antioxidant.This study aims to determine the effect of ethanol extract from Ganoderma lucidum Cianjur isolate on syndecan-1 expression in KB CCL-17 oral cell cancer. This was an experimental study with a post-test only control group design, the treatment group used G. lucidum ethanol extract with a concentration of 2.12 Î¼g/ml (P1), 4.24 Î¼g/ml (P2), and 8.49 Î¼g/ml (P3), while the positive control group used cisplatin with a concentration of 11.5 Î¼g/ml (K1). In contrast, the negative control used aquadest (K0), while syndecan-1 expression was observed using the immunohistochemical examination.The highest syndecan-1 expansion rate was found in the treatment group with a concentration of 8.49 Î¼g/ml. A significant difference was indicated by one-way ANOVA (p<0.05) between K0 - K1, K0 - P1, K0 - P2, K0 - P3, K1 - P1, K1 - P2, K1 - P3, P1 - P2, as well as P1 and P3. The administration of ethanol extract from G. lucidum Cianjur isolate increases syndecan-1 expression in KB CCL-17 oral cell cancer.